2014
DOI: 10.1177/1363460714524767
|View full text |Cite
|
Sign up to set email alerts
|

The (not so) straight story: Queering migration narratives of sexual orientation and gendered identity refugee claimants

Abstract: Canadian media coverage of sexual orientation and gendered identity (SOGI) refugees presents a relatively uniform story of these queer newcomers. While LGBT media have identified problems in some Canadian Immigration and Refugee Board (IRB) decisions, the hegemonic narrative remains one of 'migration to liberation nation'. In this article I argue that this hegemonic narrative is produced in relation to particular socio-cultural and juridical-legal categories which are themselves historically produced in and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 27 publications
(21 reference statements)
2
73
0
2
Order By: Relevance
“…Some studies suggest LGBT newcomers and refugees may not anticipate experiencing marginalization based on LGBT identity in Canada, as Canada is viewed as having human rights and protections for LGBT people, particularly compared to countries of origin where LGBT people may face punitive laws against homosexuality [ 13 , 14 ]. Murray’s qualitative study with 54 LGBT refugee claimants in Toronto, Ontario found LGBT refugees’ expectations of safety and freedom, versus the realities of immigrating to Canada, including experiencing stigma and discrimination based on their LGBT status and race/ethnicity, contributed to disappointment and stress [ 14 ]. Addressing LGBT newcomer and refugee expectations, facilitating access to the SDOH, and reducing social isolation are important factors in optimizing the health and wellbeing of LGBT newcomers and refugees.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest LGBT newcomers and refugees may not anticipate experiencing marginalization based on LGBT identity in Canada, as Canada is viewed as having human rights and protections for LGBT people, particularly compared to countries of origin where LGBT people may face punitive laws against homosexuality [ 13 , 14 ]. Murray’s qualitative study with 54 LGBT refugee claimants in Toronto, Ontario found LGBT refugees’ expectations of safety and freedom, versus the realities of immigrating to Canada, including experiencing stigma and discrimination based on their LGBT status and race/ethnicity, contributed to disappointment and stress [ 14 ]. Addressing LGBT newcomer and refugee expectations, facilitating access to the SDOH, and reducing social isolation are important factors in optimizing the health and wellbeing of LGBT newcomers and refugees.…”
Section: Introductionmentioning
confidence: 99%
“…Los discursos de rescate en el caso de las y los migrantes queer se refieren a aquellos discursos que se elaboran como 'salvataje' de una minoría que se encontraría en necesidad de protección, elementos que se ven potenciados aún más por una concepción homonacionalista de la sociedad de acogida, como abierta a lo queer, en contraposición a las sociedades homofóbicas de origen, contribuyendo, de este modo, al nacionalismo (Butler, 1993). El homonacionalismo y los discursos de rescate constituyen un campo relativamente novedoso de investigación sobre la movilidad transnacional, el que ha estado enfocado principalmente en las y los migrantes refugiados queer (Puar, 2007;Murray, 2014). Es revelador apreciar cómo estos conceptos ya aparecen en los discursos de docentes chilenos, lo que contribuye directa o indirectamente, en el caso nacional, a la racialización de la población migrante queer, más aún respecto de niñas y niños transgénero, como se observa en el siguiente relato:…”
Section: La Estigmatización De La Infancia Migrante Desde La Diferenciaunclassified
“…Claramente, y como se ha discutido a través de la evidencia internacional, la liberación de países homofóbicos de parte de las y los migrantes queer transita por la asimilación a un contexto nacional supuestamente abierto -y blanco en el caso europeo y estadounidense-, pero que invisibiliza los crímenes de odio y la discriminación de la comunidad LGBTIQ+ (Peltonen y Jungar, 2018). Ciertamente, estas situaciones de exclusión se habían encontrado en el Norte Global, específicamente en solicitantes de refugio por orientación sexual, principalmente en los países nórdicos (Murray, 2014;Akin, 2016;Peltonen y Jungar, 2018;Eggebø, Stubberud y Karlstrøm, 2018;Keskinen, 2018). A continuación, se presenta el mapa semántico de esta categoría.…”
Section: La Estigmatización De La Infancia Migrante Desde La Diferenciaunclassified
“…First, it is more pragmatic to leave undisturbed the notion that sexuality is inborn and immutable for most cases; the Immigration Equality Asylum Manual even advises lawyers to avoid phrases like "sexual preference" or "lifestyle" so as not to imply choice. These risk-reduction strategies fit readily with prevailing notions of sexuality in the Western world and are easily digestible for adjudicators (Berger 2009;Murray 2014). Second, many asylum seekers themselves view their sexualities as inborn and constitutive of their true selves.…”
Section: Findings Immutable Identities Fixed Categoriesmentioning
confidence: 99%